Across the dark water - Alvarez, Jennifer Lynn (Alvarez, Jennifer Lynn. Riders of the Realm, 2018)
Believing they have tamed all the wild winged horses, stable groom Rahkki and his Sandwen clanmates are stunned when a wild herd flies over their village, but this herd has crossed the ocean hoping to settle in a free land, unaware of the Sandwens.